(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study focuses on the corruption prevention strategy implemented by Korsupgah (Coordination and Supervision for Corruption Prevention) within the mining sector by giving emphasize on the process of reactions, learning, and behavioral changes in anti-corruption which aimed at reducing the corruption level as the result of the program. The research evaluates Korsupgah program by describing the importance of corruption prevention and measuring the effectivenss of Korsupgah Program (in the form of EPK Indices) in the mining sector reflected by anti-corruption behavioral changes of the mining actors. Herewith, the EPK indices are used as one of the criteria and indicator for corruption prevention program implementation. The study population consists of the Civil State Apparatus (ASN) in the provincial government units which are the Office of Environmental, Office of Energy and Mineral Resources (ESDM), Inspectorate, and Integrated One-Stop Service Center (Pelayanan Terpadu Satu Pintu abbreviated as PTSP) in Bangka Belitung, South Kalimantan, and South Sumatra, as well as Coordination and Supervision for Corruption Prevention (Korsupgah) Team in BPKP which in total amounting of 251 persons. The study employs a Structural Equation Model using SEM AMOS Ver. 24. The study concludes that: 1) The korsupgah capability positively and significantly affects case handling; 2) the program implementation positively and significantly affects case handling; and 3) the program implementation positively and significantly affects the capability. The study evaluates four stages of Kirkpatrick Model and confirms that: 1) Reaction: the study shows that mining actors’ response towards special purpose audit (Audit Tujuan Tertentu abbreviated as ATT) is adequate (prevention); 2) Learning: the study shows that learning process of Korsupgah Program (prevention) has been already in progress. 3) Behavior: the study shows that the behavioral change to follow up on the finding result of ATT Korsupgah has been observed. 4) Result: the study shows that the Corruption Perception Index is still low, Public Complains and corruption cases in mineral and coal mining still exist.